PENGARUH SUMBER DAN PENYALURAN KREDIT TERHADAP LABA DAN HARGA SAHAM BANK PADA BURSA EFEK INDONESIA (Studi Empiris pada Bank Umum di Bursa Efek Indonesia periode 2013 – 2016) - Rina Yuli Ningsih, Bambang Widarno & Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
This study aims to determine and analyze the influence of third party funds (DPK), credit distribution and Non Performing Loan (ROA) to the profitability (ROA) and the influence of ROA on stock prices of banks listed on the BEI. The data used in this study are the financial reports published during 2013 - 2016. This study used a sample of 30 companies with sample selection using Purposive Sampling method. The analysis tools used in this research are simple and multiplel linearregression analysis at 5% of significance level. The results showed that DPK has negative and insignificant effects on ROA. Credit distribution has positive and significant impacts on ROA. Bad credit has negative and significant effects on ROA, and ROA has positive and significant effects on stock price of bank registered in BEI on the period of 2013 - 2016.Keywords: Stock Price, ROA, DPK, Credit Distribution, NPL.